Institutional Framework: Strategic approach for Poverty reduction and Economic Growth - Egamberdiyev Xolbek Qurbonovich; Ochilova Ozoda Toshquvvatovna (Zien Journals, 2024)
Societies worldwide are struggling with a common problem, poverty. To counter this threat, the international community is constantly looking for strategies to stimulate economic growth and improve living standards. An increasingly popular approach to this end is institutional strengthening. In researching this topic, we consider the critical components of institutional strengthening such as social investment, empowerment, targeting, inclusion, safety nets, multidimensional poverty, sustainable development, global cooperation and data measurement. we go out
Keywords: Property rights; rule of law; government efficiency; effective policy implementation